The Serpent of Their Agonies: Exploitation as Structural Determinant of Mental Illness. Issue 2 (25th November 2020) - Prins, Seth J.; McKetta, Sarah; Platt, Jonathan; Muntaner, Carles; Keyes, Katherine M.; Bates, Lisa M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Social stratification is a well-documented determinant of mental health. Traditional measures of stratification (e.g., socioeconomic status) reduce dynamic social processes to individual attributes downstream of mechanisms that generate stratification. In this study, we measure one process theorized to generate and reproduce social stratification—economic exploitation—and explore its association with mental health. Methods: Data are from the 1983 to 2017 waves of the Panel Study of Income Dynamics, a nationally representative cohort study (baseline N = 3059). We operationalized "unconcealed exploitation" as the percentage of individuals' labor income they were hypothetically not paid for productive hours. We ascertained psychologic distress and mental illness with the Kessler-6 (K6) scale. Results: We fit inverse probability-weighted marginal structural models and found that for each unit increase in unconcealed exploitation, psychologic distress increased by 1.6 points (95% confidence interval = 0.71, 2.5) on the K6 scale and the odds of mental illness tripled (odds ratio = 3.0, 95% confidence interval = 1.5, 6.1). Results were not driven entirely by overwork and were robust to different inverse probability-weighted estimation strategies and sensitivity analyses. Conclusions: Exploitation is associated with mental illness. Focusing on exploitation rather than its consequences (e.g., socioeconomic status), shifts attention to a structural process that may be a more appropriate explanatory mechanism, and a more pragmatic intervention target, for mental illness.